Rational Choice Of Antibiotics For Chronic Hematogenous Osteomyelitis In Children - Musoyev Sodiqjon Toyirovich (Journal of Science in Medicine and Life, 2024)
Osteomyelitis is an infection of bones caused by various pathogens. Pathology can develop anywhere, but in children it is often diagnosed in the long bones of the limbs. Inflammation in adults usually affects the bones of the pelvis or spine. Early detection of the disease gives a chance to recover without complications, but late diagnosis can even lead to bone loss.